TOKOH ILMU BALAGHATUL QUR’AN, PENGERTIAN DAN SEJARAH BALAGHATUL QUR’AN - Dela Widya Salsa; Taufik Rizal; Ummi Annisa Gultom (Wahdatul Ulum Institute, 2026)
This paper aims to examine the definition, historical development, and prominent figures of Balaghatul Qur’an as a foundational framework for understanding the linguistic inimitability of the Qur’an. Etymologically, balaghah derives from the Arabic root balagh, meaning “to reach”, referring to the ability to convey a message precisely and impressively to the audience. Terminologically, this discipline encompasses three main branches: Ilm al-Ma’ani, which studies the conformity of sentences with their context; Ilm al-Bayan, which examines various figurative expressions such as tasybih (simile), isti’arah (metaphor), and kinayah (allusion); and Ilm al-Badi’, which addresses the aesthetic dimensions of both form and meaning. Balaghatul Qur’an specifically applies these rhetorical sciences to uncover the beauty and miraculous nature of Qur’anic language, which no human or jinn can replicate. The historical development of this science progressed gradually, beginning with the pre-Islamic Arab literary tradition, evolving during the early Islamic period as a scholarly response to the need for deeper Qur’anic understanding, reaching systematic maturity between the 3rd and 7th centuries Hijri, and undergoing methodological renewal in the modern era. Eminent scholars who made monumental contributions to this field include Abu Ubaidah Ma’mar bin Mutsanna through Majaz al-Qur’an, Al-Jahiz through al-Bayan wa al-Tabyin, Abd al-Qahir al-Jurjani through the al-nazm theory in Dala’il al-I'jaz, Al-Zamakhsyari through the al-Kasysyaf exegesis, Al-Sakkaki through Miftah al-‘lum, and Ali al-Jarim and Mustafa Amin through al-Balaghah al-Wadhihah in the modern period.